Developmental trends of divergent thinking and feeling across different grades for Taiwanese adolescence between 1990's and 2010's. (March 2017) - Chang, Yu-Lin; Chen, Hsueh-Chih; Wu, I-Chen; Chang, Jen-Ho; Wu, Ching-Lin
Highlights: This study focused on Taiwanese students developmental trends of cognitive and affective creativity. The divergent thinking was significantly enhanced as grade increased while the divergent feeling only slightly enhanced. The fluctuation of developmental trend of divergent thinking scores during 1994-1998 was larger than the current trend. Divergent feeling scores between current and 1990's showed a similar linear upward trend. Abstract: Previous studies regarding developmental trends of creativity in adolescence rarely focused on both cognitive and affective factors of creativity. In Taiwan, the survey in this field also lacked during these two decades. Therefore, this study aimed to understand Taiwanese students' developmental trends of creativity in both cognitive and affective aspects. The researchers analyzed the difference between divergent thinking and divergent feeling of Taiwanese adolescent students across different grades as well as the linear trend. The difference of divergent thinking and divergent feeling scores between this study and the 1990s' was also examined. Participants included 1674 fifth-grade to eleventh-grade students (866 boys, 51.73%). The results showed that divergent thinking scores as cognitive aspect significantly enhanced as grade levels increased. The divergent feeling scores as affective aspect slightly enhanced as grade levels increased, but slumped in the sixth grade and steeply ascended in the eleventh grade. When the divergent thinking scores of the current students were compared with the scores of the students in 1990s, the types of developmental trend were different, which was the fluctuation of developmental trend was larger than the current trend which was smoother. The mean scores of current participants for each grade level had less variation than 1990s'. The divergent feeling scores in both 1990s' and 2010s' increase and showed a similar linear upward trend. The results would suggest further investigation and promotion of creativity in education policy.